Risk stratification of adolescents for the screening of non‐alcoholic fatty liver disease. Issue 9 (2nd May 2022) - Abrams, Gary A.; Ware, Deanna; Byrne, Margaret M.; Hecht, Eric M.
Summary: Background: Non‐alcoholic fatty liver conditions in adolescence are associated with premature mortality in adulthood. Effective screening could impact the population burden of this disease. Objectives: We sought to determine which adolescents should be screened for non‐alcoholic fatty liver using vibration‐controlled transient elastography. Methods: We simulated a non‐alcoholic fatty liver screening program of 938 adolescents from the National Health and Nutritional Examination Survey of 2017/2018. We stratified subjects by body mass index and metabolic parameters and analyzed our data using standard diagnostic statistical measures. Results: The weighted prevalence of non‐alcoholic fatty liver and non‐alcoholic fatty liver disease was 24.4%, and 3.8%, respectively. For all subjects with obesity (21.8% of the population), screening identified 61.8% of the non‐alcoholic fatty liver cases. In a category of all subjects with obesity and overweight subjects with metabolic abnormalities (26.7% of the population), screening identified 71.2% of non‐alcoholic fatty liver cases. Conclusions: The two groups most likely to benefit by transient elastography screening are adolescents with obesity and overweight adolescents with one metabolic abnormality. These criteria reduce the number of individuals to be tested by approximately 80% (from an approximate 32 million adolescents to 6–7.5 million adolescents), while retaining a diagnostic accuracy of 84%–85%.